Functional evaluation following deltoid muscle resection in patients with soft tissue sarcoma. (6th April 2020) - Hamada, Shunsuke; Nishida, Yoshihiro; Takanari, Keisuke; Ota, Takehiro; Urakawa, Hiroshi; Ikuta, Kunihiro; Sakai, Tomohisa; Tsukushi, Satoshi; Kamei, Yuzuru; Ishiguro, Naoki
Abstract: Background: The present study aimed to determine functional outcomes in patients undergoing deltoid muscle resection for soft tissue sarcoma. Methods: Between 2002 and 2014, 18 patients with soft tissue sarcoma of the shoulder who underwent wide resection including the deltoid muscle, and were followed up for more than 12 months, were retrospectively included in the study. In all, 11 patients were male and 7 were female. The median age was 59 years, median follow-up duration was 37 months. The extent of resection of deltoid muscle, with or without rotator cuff damage, reconstruction methods, adjuvant therapy, oncological outcomes, and the International Society of Limb Salvage (ISOLS) score as functional outcomes were analyzed. Results: Six patients underwent total resection, and twelve underwent partial resections of deltoid muscle. The rotator cuff was resected in four patients. Soft tissue reconstruction was performed in 17 patients using a pedicled latissimus dorsi muscle flap. Two local recurrences and three distant metastases occurred during follow-up. Median overall survival was 72 months. The mean ISOLS score was 25.0 points (±4.6points). Univariate analysis revealed that there was no significant difference in ISOLS score regarding the extent of deltoid muscle resection. Multivariate analysis identified only combined resection of the rotator cuff as a significant prognostic factor for poor functional outcomes ( P  < 0.001). Conclusions: The extent of resection of the deltoid muscle might not affect the functional outcomes determined by ISOLS score. If the rotator cuff is resected concurrently, satisfactory functional outcomes might not be obtained. Abstract : The functional outcome following deltoid muscle resection in patients with soft tissue sarcoma was evaluated. If the rotator cuff is resected with deltoid muscle, satisfactory functional outcomes might not be obtained.